Comparative Study of Physical Activity: Chronic Disease Management Program (Prolanis) Exercises on Diabetes Mellitus of Type 2 - Yusniar Yusniar; Esrina Sinaga (Universitas Islam Negeri Sumatera Utara, Medan, 2024)
Fatigue, weakness and various musculoskeletal problems in people with type 2 diabetes (T2DM) can be overcome by regular, low-impact physical activity. The Indonesian government has a Physical Activity; Chronic Disease Management Programme (Prolanis) that can overcome musculoskeletal problems while maintaining stable blood glucose levels in T2DM. This study is qualitative phenomenology with a population of T2DM patients actively visiting the Aek Habil Health Centre area in Sibolga City, the research was conducted for approximately six months. Participants were six samples divided into two groups, purposive sampling technique, data collection process through interviews, observation and documentation methods, analysis and testing using triangulation, aiming to compare T2DM patients who follow physical activity; prolanis with patients who do not follow the programme. Results and conclusions: There were no differences in health complaints and differences in blood glucose levels in the two groups of participants, there were differences in physical description and quality of life in the group that did not participate in prolanis physical activities. Suggestion: It is necessary to evaluate and approach to improve the programme for T2DM patients who do not do physical activity; prolanis exercise.Keywords: DMT2, Exercises (Prolanis), Physical activity